2008
DOI: 10.2174/092986608785203656
|View full text |Cite
|
Sign up to set email alerts
|

Aptabodies – New Type of Artificial Receptors for Detection Proteins

Abstract: We report on a new type of artificial receptor formed by hybridization of two DNA aptamers for human thrombin (aptabody). This aptasensor based on multiwalled carbon nanotubes allowed us to detect thrombin with detection limit of 0.3 nM, which was 3 times better in comparison with conventional aptamer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Recently, we proposed a simple method for aptamer engineering based on DNA hybridization of the supporting part of the DNA aptamers. This results in the formation of an aptamer dimer, so called here an aptabody, analogous to antibodies, which also possesses two binding sites [5].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we proposed a simple method for aptamer engineering based on DNA hybridization of the supporting part of the DNA aptamers. This results in the formation of an aptamer dimer, so called here an aptabody, analogous to antibodies, which also possesses two binding sites [5].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In comparison to canonical aptamers with one binding site, the aptamer dimers display better detection limit and binding constant to human thrombin [5]. It has been also shown that engineered aptamers like multivalent circular constructs exhibit increased stability against cleavage by exonucleases and improved (2 to 3-fold) anticoagulant activity in comparison with canonical single stranded aptamers [8].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This supporting part has resulted in a wider structural diversity of aptamers through the formation of aptamer dimers, as was discussed simultaneously by Hasegawa et al (2008) and Hianik et al (2008). Hasegawa et al (2008) described two aptamers sensitive to fibrinogen and heparin binding sites of thrombin which contained poly dT linkers connected by DNA ligase.…”
Section: Structural Polymorphism Of Guanine Quadruplexes and Their Phmentioning
confidence: 92%
“…Fluctuations in the oscillation frequency of the quartz crystal which reflect both mass and viscosity changes at the crystal surface were measured during cycling of the voltage in the range of -0.7 to + 0.6 V (vs. Ag/AgCl reference electrode) a process which aided the interaction between thrombin and the DNA aptamers. This method has substantially improved the thrombin detection limit; while conventional QCM methods with aptamers immobilized by avidin-biotin technology resulted in thrombin detection with a LOD of 10 nM (Hianik et al 2005), the immobilization of aptamers on the MWCNTs-MB composite layer and simultaneous cycling of the voltage resulted in a LOD of 0.3 nM (Evtugyn et al 2008b;Hianik et al 2008). In our work we showed higher sensitivity of aptasensor based on aptamer dimers (aptabodies) in comparison to the conventional single-stranded aptamers (Fig.…”
Section: A C Bmentioning
confidence: 99%